Syntheses of Azo-Imine Derivatives from Vanillin as an Acid Base Indicator - Bambang Purwono; Chairil Anwar; Ahmad Hanapi (Universitas Gadjah Mada, 2013)
Preparations of azo, imine and azo-imine derivatives from vanillin as an indicator of acid-base titration have been carried out. The azo derivative of 4-hydroxy-3-methoxy-5-(phenylazo)benzaldehyde 2 was produced by diazotitation reaction of vanillin in 37.04% yield. The azo product was then refluxed with aniline in ethanol to yield azo-imine derivatives, 2-methoxy-6-(phenylazo)-4-((phenylimino)methyl)phenol 1 in 82.21% yield. The imine derivative, 2-methoxy-4-((phenylimino)methyl)-phenol 3 was obtained by refluxing of vanillin and aniline mixture in ethanol solvent and produced 82.17% yield. The imine product was then reacted with benzenediazonium chloride salt. However, the products indicated hydrolyzed product of 4-hydroxy-3-methoxy-5-(phenylazo)benzaldehyde 2 in 22.15% yield. The 2-methoxy-4-((phenylimino)methyl)phenol 2 could be used as an indicator for titration of NaOH by H2C2O4 with maximum concentration of H2C2O4 0.1 M while the target compound 1 could be used as titration indicator for titration of NaOH with H2C2O4 with same result using phenolphthalein indicator.